Analyzing the outdoor degradation behavior of organic solar modules in North China - Liu, Shaopeng; Zhang, Dawei; Egelhaaf, Hans-Joachim; Wang, Gaoyuan; Li, Xiaogang; Heumüller, Thomas; Brabec, Christoph; Li, Ning (Journal of Materials Chemistry A, 2024)
The outdoor stability of organic solar modules (OSMs) directly determines the success of the organic photovoltaic (OPV) technology, which is critically important but insufficiently studied so far. Here, we perform a systematic study on the long-term outdoor exposure of OSMs according to the ISOS-O-2 standard lasting over two years. OSMs featuring a large active area (108 cm2), lightweight design (∼22 g), and typical PCE value (4.2%) were utilized in this study. The environmental data and OSMs' property data are synchronously collected to investigate the relationship between the outdoor properties of OSMs and environmental factors with the aid of machine learning and traditional mathematical methods. Based on the experimental results, we quantify the OSMs' degradation process and evaluate the long-term stability of OSMs. Encouragingly, we find that the long-term operational stability of OSMs is quite impressive under the outdoor aging conditions in North China. The initial outdoor PCE value was around 4%, maintaining over 3.3% even after two years of outdoor exposure. The extrapolated degradation rate remained below 2% per year, despite the burn-in process. The observed burn-in process during outdoor degradation suggests that mitigating burn-in loss could enhance the field stability of OSMs, and that the outdoor environment can be effectively simulated in a well-designed laboratory setting for stability studies. All of this suggests a bright future for further development of OPV technology towards commercialization and practical outdoor applications.
CRIS-Team Scopus Importer:2024-05-31